2016
DOI: 10.1016/j.jpainsymman.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Care Professionals' Attitudes Toward Systematic Standardized Symptom Assessment and the Edmonton Symptom Assessment System After Large-Scale Population-Based Implementation in Ontario, Canada

Abstract: Findings show significant albeit variable uptake across disciplines in the use of the ESAS since program initiation. Several barriers to using the ESAS in daily practice were identified. These need to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 43 publications
3
71
0
5
Order By: Relevance
“…(75) A patient satisfaction survey involving 3660 patients in Ontario reported that a vast majority of patients (92%) agreed that the ESAS was important “as it helped their healthcare team to know their symptoms and severity”. (76)…”
Section: Present Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(75) A patient satisfaction survey involving 3660 patients in Ontario reported that a vast majority of patients (92%) agreed that the ESAS was important “as it helped their healthcare team to know their symptoms and severity”. (76)…”
Section: Present Applicationsmentioning
confidence: 99%
“…(77) A subsequent survey of 2806 oncology professionals in Ontario (response rate 38%) also found that a majority of physicians (67%) and nurses (85%) perceived ESAS to be a useful starting point to assess patients’ symptoms. (76) 79% of physicians reported that they reviewed the ESAS scores at visits either “always” or “often”. However, a separate chart audit found that only 29% of patients with moderate-to-severe pain and 6% of patients with moderate-to-severe dyspnea had clinical actions documented in the chart, suggesting the need to strengthen the downstream actions from symptom screening through clinician education, resource allocation, and care pathways.…”
Section: Present Applicationsmentioning
confidence: 99%
“…In addition is the challenge of implementing evidence‐based psychosocial interventions . In one study, 30% of health care/medical professionals reported rarely or never looking at screening scores and only 60% discussed the scores with their patients . Screening alone is ineffective if the distress is not addressed with some form of psychosocial intervention …”
Section: Introductionmentioning
confidence: 99%
“…While attempts have been made to integrate distress management through screening programs, there is a discrepancy between the attitude and actual practice . Time, appropriate space needed to address private concerns and emotional distress identified in psychosocial screening, and skill are often cited as barriers by health care providers .…”
Section: Introductionmentioning
confidence: 99%
“…A case has also been made for a palliative care approach to be provided by family physicians 10 . Most oncologists and oncology nurses acknowledge a role in providing the palliative care approach to their patients 11 .…”
mentioning
confidence: 99%